Sorpsi Isotermik Daun Krokot (Portulaca oleracea L.) dan Pendugaan Umur Simpan dengan Metode Accelerated Shelf Life Test (ASLT) Model Arrhenius - Syska, Kavadya; Arifah, Ika Nur; Ropiudin, Ropiudin; Najib, Akmal Auladi; Aulia, Risfa; Ayuningtyas, Syella Aditya; Istiqomah, Kholifatun; Pranoto, Restu Aji Saripwijaya; Hakim, Ahmad (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2025)
Purslane (Portulaca oleracea L.), commonly known as purslane, is a medicinal plant traditionally utilized by Indonesian communities and holds significant potential for development as an herbal tea product. The leaves contain key bioactive compounds such as flavonoids, antioxidants, and tannins, which contribute to their pharmacological properties. One of the scientific approaches to evaluate the stability and shelf life of products derived from purslane leaves is through water sorption isotherm analysis (ISA), which represents the relationship between equilibrium moisture content and water activity (aw) at a constant temperature. Understanding the sorption isotherm characteristics of a product is critical for selecting appropriate packaging materials and designing optimal storage conditions to extend shelf life. In this study, the water sorption behavior of dried purslane tea was modeled using the Guggenheim–Anderson–de Boer (GAB) model. The isotherms were generated using saturated salt solutions to obtain a range of water activity values from 0.05 to 0.90 at a constant temperature of 30°C. For shelf life estimation, dried purslane tea samples were packed in three different packaging materials: aluminum foil, high-density polyethylene (HDPE), and polypropylene (PP), and stored under two controlled temperature conditions, 10°C and 30°C, for 28 days. Quality changes, particularly in moisture content, were monitored at weekly intervals. The results showed that equilibrium moisture content increased with increasing water activity, consistent with the typical behavior of hygroscopic materials. The GAB model adequately described the water sorption isotherm pattern of purslane tea. Shelf life estimations based on 4-week storage data indicated that at 10°C, aluminum foil packaging provided the most effective barrier against moisture uptake compared to HDPE and PP, although specific shelf life values were not reported at this temperature. In contrast, at 30°C, PP-packaged samples exhibited the longest predicted shelf life of 528 days, followed by HDPE at 310 days. Shelf life projections obtained using the Accelerated Shelf Life Testing (ASLT) method with the Arrhenius model suggest that aluminum foil packaging generally offers superior protection and shelf life extension compared to HDPE and PP.